CONSOLIDATED COST ACCOUNTING AT MEAT AND FAT PRODUCTION: METHODOLOGY AND PRACTICE - Kushnir , V.O. (The actual problems of regional economy development, 2017)
Aim of the article is to study and improve methods of consolidated cost accounting at meat and fat production to obtain detailed information about production costs and to find ways to reduce the cost of meat production. It is offered to account expenses at meat and fat department for individual production areas that will receive detailed information for the purposes of control, analysis, calculation and reporting. For expedient budgeting activities of each structural unit of meat and fat production and for needs to saving production is proposed to reflect the costs of each production plant to separate groups of analytical accounts.